PENGARUH PERAN GURU DAN EVALUASI PEMBELAJARAN TERHADAP PRESTASI SISWA DI SDN 01 NUSA BAKTI - Khasbi Ainun Najib; Siti Aisyah; Aprilia Cahya Neng Tyas (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to examine the influence of teachers’ roles in learning evaluation on elementary school students’ academic achievement. Evaluation is a crucial component of the learning process, serving as a tool to measure learning objectives and as a basis for decision-making in improving educational quality. Teachers play a vital role in determining the form, timing, and method of evaluation. The main issue explored in this research is the extent to which teacher involvement in learning evaluation affects students' academic performance. The research uses a descriptive quantitative approach with data collection techniques such as questionnaires, observations, and documentation. The findings reveal that teachers who are actively and systematically involved in the evaluation process can significantly improve students’ learning outcomes. Therefore, enhancing teachers’ competence in conducting evaluations is essential to support student success in elementary education.